2021
DOI: 10.1186/s13643-021-01843-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to physical activity in patients during hospital stay: a scoping review

Abstract: Background Low levels of physical activity are common during the hospital stay and have been associated with negative health outcomes. Understanding barriers and enablers to physical activity during a hospital stay can improve the development and implementation of tailored interventions aimed at improving physical activity. Previous studies have identified many barriers and enablers, but a comprehensive overview is lacking. This study aimed to identify and categorize all published patient- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 108 publications
5
44
0
1
Order By: Relevance
“…Modifiable factors at the institutional level, including sufficient resources, stimulating physical environment, and patient activities, were also reported in previous research and multidimensional interventions were suggested [ 27 29 , 91 , 100 ] which is in line with our results. Our review showed that multidimensional intervention studies, including an increase of resources, adding ambulation pathways, or monitoring physical functioning, might result in positive effects on patients’ step count per day [ 72 , 80 ], or faster recovery of physical functioning [ 79 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Modifiable factors at the institutional level, including sufficient resources, stimulating physical environment, and patient activities, were also reported in previous research and multidimensional interventions were suggested [ 27 29 , 91 , 100 ] which is in line with our results. Our review showed that multidimensional intervention studies, including an increase of resources, adding ambulation pathways, or monitoring physical functioning, might result in positive effects on patients’ step count per day [ 72 , 80 ], or faster recovery of physical functioning [ 79 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [ 27 , 29 , 91 ], the importance of awareness and knowledge about mobilization to improve patients’ PA behavior was recognized in the current review. However, when it comes to prioritizing poor health status or fear of falling, it seems that safety and zero-fall policies can sometimes take precedence over the known benefits of mobility.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Family caregivers (FCs) are often responsible for supporting their relative's recovery after hospital discharge. While healthcare providers have identi ed FCs as potential facilitators of patients' engagement in physical activity [5,6], very few studies have examined FCs' perspectives on their preparedness to support the physical activity of a relative. Furthermore, no studies have focused speci cally on FCs of patients at risk for hospital readmission in rural communities.…”
Section: Introductionmentioning
confidence: 99%